CULTURAL CREATIVITY AS A SPHERE OF FORMATION OF POLITICAL VALUES: THEATER IN FRONT-LINE KHARKIV - Komarova, Tetiana; Kononenko, Valery (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The article examines the peculiarities of cultural creativity in Kharkiv under the conditions of the armed invasion of Ukraine by the Russian Federation. The peculiarity of Kharkiv as a border and now front-line city is emphasized, which left its mark on all spheres of its life, revealing its limitations and risks. The intertwining of political practice with the production of cultural phenomena and with culture in general is noted. Power is characterized as the key pillar of politics, which in the information age is primarily determined by the production and control of value meanings and cultural codes of society. The change in the technology of exercising power is revealed - from authoritarian coercion to mimicry to fulfill the needs of seducing the consumer of political products in order to reduce his critical thinking. The authors emphasize that for a socially healthy, comfortable society, a certain interaction of symbolic and meaningful images in the information space is important, as is a sufficiently stable system of axiological meanings, principles of social understanding, and support for a common socio-cultural field that contribute to the existence of a stable identity of citizens of a certain country. Theater as a form and method of cultural creativity opens up possibilities for synthesizing the forces of tradition and modernization, which, according to the authors, is a necessary condition for the successful adaptation of society under the conditions of rapid and largely radical transformations of the information age. Changes in the functioning of Kharkiv’s art institutions under martial law are analyzed. Despite objective restrictions related to security, numerous theaters, concert venues, and cultural centers did not stop their activities, seeking new formats of work under war conditions. The experience of Kharkiv artists is highlighted, which testifies to the importance of culture as a means of psychological resilience of society and demonstrates unique practices of adapting art to the realities of wartime. The events take place in safe spaces, in basements and bomb shelters. Attention is focused on the fact that Kharkiv theater figures are impressive in their dedication to their work, often treating it as a volunteer activity, working not for material gain, but for the sake of their beloved profession, the audience, and dedication to the common cause of social prosperity, at least for the future. It is noted that cultural resistance is becoming an equally important component of the national struggle, and the examples of Kharkiv are symbols of resilience and faith in the Renaissance.